Investigation of Lightweight Concrete Filled Sawdust for Thermal Properties - Ibrahim, Muhamad I'zaz Syafwan; Kamarul Aini Mohd Sari (Progress in Engineering Application and Technology, 2024)
This study investigates the potential of sawdust as a sustainable alternative to sand in lightweight concrete production. The research focuses on evaluating the effects of incorporating sawdust as a fine aggregate on the compressive strength and thermal conductivity of lightweight concrete. This research are to identify the optimum proportion of lightweight concrete filled sawdust and pumice analysed the physical and thermal properties of lightweight concrete.The proportion of sawdust in LWC have been used in this research were 25%, 50%, 75% and 100% of sawdust. The compressive strength tests revealed a consistent decrease in strength as the percentage of sawdust increased, with the highest strength recorded for the 25% sawdust mix .Furthermore, the thermal conductivity was recorded that 75% sawdust, the thermal conductivity is 0.245(W/mK). Overall, the study underscores the potential of sawdust as a promising eco-conscious option in the realm of construction materials